2017
DOI: 10.1177/2333721417709578
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence and Nocturia in Older Adults After Hip Fracture: Analysis of a Secondary Outcome for a Parallel Group, Randomized Controlled Trial

Abstract: Objective: To test the effect of a follow-up clinic on urinary incontinence (UI) and nocturia among older adults with hip fracture. Method: Fifty-three older adults (≥65 years) 3 to 12 months following hip fracture were enrolled and randomized to receive usual care plus the intervention (B4), or usual care (UC) only. The B4 group received management by health professionals, with need-based referrals. UI, nocturia, and quality of life were measured with questionnaires at baseline, 6 months, and 12 months. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…All 22 studies used the ICECAP-O alongside other measures and in all but four studies [ 15 , 51 , 53 , 56 ] this included the EQ-5D.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 22 studies used the ICECAP-O alongside other measures and in all but four studies [ 15 , 51 , 53 , 56 ] this included the EQ-5D.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen of the 20 studies that generate an ICECAP-O tariff value also calculate either the change in ICECAP-O score induced by the treatment, or the component figures needed to calculate the change. One study [ 66 ] does not present results by arm due to the small sample size (this was a pilot/feasibility study) and one study [ 53 ] presents the correlation between presence of the condition and capability at baseline and follow-up. All but one of these 18 studies solely presents the results in tabular form alongside the corresponding results for other measures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary incontinence (UI) is another highly prevalent geriatric syndrome among older patients with hip fracture. In a randomized clinical trial, 44% of study participants self-reported UI and four out of five reported nocturia at baseline [ 62 ]. A cohort study demonstrated that UI was associated to an increased risk of falls, but not of hip fractures [ 63 ].…”
Section: Resultsmentioning
confidence: 99%